LEIOMYOMA OF THE VAGINA - Hameed, Nazli (Journal of Ayub Medical College Abbottabad, 2003)
A vaginal leiomyoma is normally a benign smooth muscle tumour in the vagina. These tumours are extremely rare and the aetiology is unknown. The imaging findings are those of a nonspecific well-defined enhancing soft tissue mass centred on the vagina. The lesion may be very large, but is usually under 6 cm in size. Patients are asymptomatic in the early stages. Symptoms arise with the growth of tumour mainly due to compression. Most leiomyomas are not diagnosed clinically but only on histological examination. A case of primary leiomyoma of vagina is presented here.